2015
DOI: 10.18178/ijfe.1.1.23-28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Thermal Processing on Allergenicity Proteins in Bombay Locust (Patanga Succincta)

Abstract: Food security is importance for people all the world. Bombay locust (Patanga succincta) is a major agricultural pest in Thailand and most popular for consumption as human food. Arthropods include crustacean (shrimp) and insect which can induce allergic reactions in sensitive humans. The aims of this study is to identified the cross-reactive allergens in P. succincta with sera who allergic to shrimp by IgE-immunoblotting and tandem mass spectrometry (LC-MS/MS) and investigated the effect of thermal processing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
(18 reference statements)
1
26
0
Order By: Relevance
“…cockroaches) [60][61][62]. The studies performed with edible insects [35][36][37][39][40][41][42] further confirmed the role of tropomyosin and AK as cross-reacting allergens with crustaceans, although other known arthropod allergens (GADPH, myosin light chain, fructose-biphosphate aldolase, actin, ␣-tubulin, ␤-tubulin) have been identified. Hexamerin was also identified as a cross-reacting allergen with crustaceans in studies performed with the Bombay locust [39] and field cricket Gryllus bimaculatus [40].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…cockroaches) [60][61][62]. The studies performed with edible insects [35][36][37][39][40][41][42] further confirmed the role of tropomyosin and AK as cross-reacting allergens with crustaceans, although other known arthropod allergens (GADPH, myosin light chain, fructose-biphosphate aldolase, actin, ␣-tubulin, ␤-tubulin) have been identified. Hexamerin was also identified as a cross-reacting allergen with crustaceans in studies performed with the Bombay locust [39] and field cricket Gryllus bimaculatus [40].…”
Section: Discussionmentioning
confidence: 80%
“…The studies performed with edible insects [, ] further confirmed the role of tropomyosin and AK as cross‐reacting allergens with crustaceans, although other known arthropod allergens (GADPH, myosin light chain, fructose‐biphosphate aldolase, actin, α‐tubulin, β‐tubulin) have been identified. Hexamerin was also identified as a cross‐reacting allergen with crustaceans in studies performed with the Bombay locust and field cricket Gryllus bimaculatus . Although hexamerin is not identified as a crustacean allergen, it belongs to the same superfamily as hemocyanin which is a crustacean allergen.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As an example, heat treatments can alter the protein structure, so triggering or shutting down the allergenicity of specific compounds. This effect has been documented by Phiriyangkul et al (2015) who described a change in the allergenic profile of a locust species, Patanga succincta, when consumed raw or processed (fried). Similarly, the allergenic profile of crickets could be substantially different depending on the food processing technique used.…”
Section: Allergiesmentioning
confidence: 75%